The prevalence of Epilepsy and its co-occurrence with alcohol dependence among polish prisoners - Barbara Stawińska-Witoszyńska; Katarzyna Czechowska; Barbara Więckowska (BMC, 2019)
Abstract Background For a large part of the prisoners population, the prevalence of many diseases and the number of risk factors are greater than for the general population. In this work, we present an analysis of the prevalence of epilepsy and its co-occurrence with alcohol dependence among prisoners in a Polish penitentiary. Methods One and multidimensional logistic regression was used to present the relationship between epilepsy and the co-occurrence of alcohol dependence and of other variables like: the prisoners' age, their classification, the unit type, the length of the stay in the penitentiary, and professional activity. Results More than 7% of the prisoners had epilepsy. The prevalence was significantly higher in the 40-49 age group and among prisoners aged 50 and older. For prisoners suffering from alcohol dependence, the probability of epilepsy was over four times higher than for prisoners who did not suffer from that condition (OR [95%CI] = 4.09 [1.82-9.17], p = 0.001]. Conclusions The obtained results show that the prevalence of epilepsy and alcohol dependence in the studied prisoner population was much higher than in the general population of Poles and that alcohol dependence was strongly correlated with epilepsy, independent from other variables. The research allowed to assess the size of the analyzed problem among convicts, however, bearing in mind the multifactorial etiology of epilepsy, the cause and effect relationship between exposure to alcohol and its occurrence would require further in-depth analytical studies taking into account other etiological factors of this disease.